KAJI EKSPERIMENTAL MATERIAL KOMPOSIT BERPENGUAT SERAT DAUN NANAS PADA PENGUJIAN BALISTIK - Galindra Mutiara Rahmatullah; Boy Rollastin; Juanda Juanda (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
The pineapple plant is one of the most prominent plants in Indonesia, the value of the pineapple leaf could be said to have no sell or be called a waste. The use of composite materials with natural fiber filtering is growing. Composites are materials made up of two or more different materials. In this study used epoxy particle composites with doubles of the hollow glass microsphere and fibers of the pineapple leaves. In this research conducted a 3 thickness test of 10 mm, 15 mm, and 20 mm. The test results were obtained that projectile-pierced specimens with depth damage after penetrating the succeeding specimens of 58 mm, 10 mm and 4 mm. From the results is obtained, specimens were not safe to use because according the criteria for failure of bulletproof vest from the aspect of penetration is penetration should not exceed from thick vest or can be said sould not a translucent.